Energy optimization of a light projection system for buildings that virtually restores artworks. (March 2020) - Vázquez, D.; Fernández-Balbuena, A.A.; Canabal, H.; Muro, C.; Durmus, D.; Davis, W.; Benítez, A.; Mayorga, S.
Abstract: The need to achieve energy efficiency standards in the lighting systems of buildings makes it necessary to optimize all aspects of them. Here, the development of a light projection system that achieves this goal by studying and modifying the spectral output, compared to conventional illumination, is described. A lighting system that estimates the reflectance characteristics of artwork and emits optimized lighting can reduce light absorption. A damage-minimizing point-by-point light projection system is developed using an optimization algorithm, to improve the appearance of the surfaces of artworks whose color has faded. In this case, a simulation of an aged oil painting was made by manipulating the original photograph, which was printed and to which the proposed system was applied. The results show that, when the aged printed image is illuminated with the optimized light source, it appears indistinguishable from the non-aged oil painting. Highlights: Light projection system that damage-minimizing point-by-point. Optimized light system that allows to vary the color to achieve a desired effect. A lighting system that estimates the reflectance characteristics of the artworks and emits optimized lighting. Development of a methodology that improves the characteristics of the illuminants used. Global risk factor can be a right parameter for understanding the illumination action.